Public-private relationship in surgical hospitalizations through the Unified Health System - Liane Alves de Sá; Eduardo Rocha Covre; Willian Augusto de Melo; Rogério Miranda Gomes; Maria Fernanda do Prado Tostes (Universidade de São Paulo, 2021)
Objective: to characterize surgical hospitalizations, length of stay, cost and mortality, according to the legal nature (public and private) of the hospital institution linked to the Unified Health System (Sistema Único de Saúde, SUS). Method: a descriptive study, of the survey type, with retrospective data collection (2008 to 2017) and a quantitative approach. The dependent variables surgical hospitalizations in Brazil, costs, length of stay and mortality and the independent variables regime/legal nature (public and private) were obtained from the Informatics Department of the Unified Health System. The Mann-Whitney test was used for analysis. Results: the average number of hospitalizations through the Unified Health System was 4,214,083 hospitalizations/year, 53.5% occurred in private hired hospitals and 46.5% in public hospitals (p=0.001). The financial transfer was greater for the private sector (60.6%) against 39.4% for the public (p=0.001). The average stay was 4.5 days in the public hospital and 3.1 days in its private counterpart (p<0.001). Mortality was higher in the public (1.8%) than in the private hospital (1.4%) (p<0.001). Conclusion: there was predominance of surgical hospitalizations through the Unified Health System in private hospitals with greater financial transfer to this sector, to the detriment of the public. The diverse evidence produced contributes to the debate and actions to avoid budgetary asphyxiation in the public sector in favor of the private sector.